Results of 23 years of selection for post-weaning weight in a Caracu beef herd - Pereira, M. C. [UNESP]; Mercadante, M. E. Z.; Razook, A. G.; Figueiredo, L. A.; Albuquerque, Lucia Galvão de [UNESP] (South African Journal of Animal Sciences, 2008)
Data from 1 698 animals belonging to all experimental Caracu herd were analysed with the objective of calculating the Population selection differentials, generation intervals, effective size and inbreeding coefficients, and to estimate the direct and correlated responses for growth traits after 23) years of selection for post-weaning weight. The following traits were analysed: birth weight (BW), weaning weight corrected to 2 10 days of age (W210), weight corrected to 378 days for the males (W378), weight corrected to 550 days for the females (W550) and hip height for the males (HGTm) at the end of a feedlot test, and for the females (HGTf) at 550 days of age. The sire (W378) and dam (W550) weighted selection differentials for post-weaning weight were 1.10 and 0.28 standard deviation units and generation intervals 5.2 and 6.2 years, respectively. Mean inbreeding coefficient increased in the last five years, from 0.49 to 1.95%. The heritability estimates were 0.38, 0.27, 0.36, 0.37, 0.35 and 0.41 for BW, W210, W378, W550, HGTm and HGTf, respectively. The annual genetic trend estimates were 0.98 +/- 0.17 kg/year for W378 and 0.27 +/- 0.15 kg/year for W550. The estimates for the correlated responses to selection were 0.08 +/- 0.02 kg/year for BW, 0.48 +/- 0.11 kg/year for W210, 0.06 +/- 0.02 cm/year for HGTm and 0.02 +/- 0.02 cm/year for HGTf. These results confirmed that direct selection for post-weaning weight based oil individual performance was relatively effective in achieving progress in all the growth traits.
Keywords: Beef cattle; Creole bovine; experimental herd; genetic trend; tropical adapted breed